The Impact of ChatGPT on the Transformation of Traditional Education from the Perspective of Constructivism - Han, Yumo (Transactions on Social Science, Education and Humanities Research, 2024)
Technological products with artificial intelligence, such as ChatGPT, have revolutionized today’s education and spurred many debates on how to modify traditional teaching methods to a more modern approach. Since technology-facilitated learning has gained popularity recently, it is worthwhile to investigate the effects of AI products – particularly ChatGPT – on educators and learners as well as a number of instructional issues. This paper, which adopts a constructivist viewpoint, begins by elaborating on the instructional activities that involve both teachers and students. It then addresses the effects on each group of educators from two angles: the ways in which ChatGPT is influencing traditional education and the ways in which it is accelerating its reform. This study concludes that ChatGPT can help students learn and compensate for the shortcomings in educators’ instruction. However, there are also problems with ChatGPT’s instructional activities, such as a loss in students’ initiative in learning and a danger to teachers’ authority. This study offers a reference for future research on the use of constructivism and the transition from dualism to trialism in education and teaching.